2008
DOI: 10.1093/jn/138.2.305
|View full text |Cite
|
Sign up to set email alerts
|

Associations of Dietary and Serum Copper with Inflammation, Oxidative Stress, and Metabolic Variables in Adults ,

Abstract: There are conflicting data on the associations between copper and glycemia, plasma lipids, and atherosclerotic diseases.Copper has both pro-oxidant and antioxidant effects. We performed a cross-sectional analysis to investigate the associations between dietary copper intake and metabolic variables and serum high-sensitivity C-reactive protein (hs-CRP) in asymptomatic subjects from a population-based cohort (n ¼ 1197) and between serum copper concentration and markers of oxidative stress, including plasma nitro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
81
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 149 publications
(92 citation statements)
references
References 33 publications
9
81
0
2
Order By: Relevance
“…Incremental changes of inflammatory biomarkers have been associated with augmented plasma Cu 26 . Approximately 90-95% of the total circulating Cu are bound to ceruloplasmin 7 , whose concentrations are elevated in response to inflammation, infection and various chronic diseases 6,7 .…”
Section: Discussionmentioning
confidence: 99%
“…Incremental changes of inflammatory biomarkers have been associated with augmented plasma Cu 26 . Approximately 90-95% of the total circulating Cu are bound to ceruloplasmin 7 , whose concentrations are elevated in response to inflammation, infection and various chronic diseases 6,7 .…”
Section: Discussionmentioning
confidence: 99%
“…[4]). Moreover, more recent studies reported statistically significant associations of dyslipidemia with marginal copper and iron deficiencies [5,6], whose molecular bases and regulatory events are still largely unknown. A microarray differential analysis of gene expression, in rat intestine of animals fed on copper-or iron-deficient diets, confirmed significant changes of transcript levels of genes involved in the pathways of fatty acids (FA) and cholesterol (CL) metabolism, thus leading to the identification of molecular targets affected by the dietary deficiencies.…”
Section: Introductionmentioning
confidence: 99%
“…Data concerning the association between adipokine levels and copper consumption is scarce, however, copper and adiponectin are involved in several similar metabolic processes including oxidative defense system and glycemic control, in which the levels of adiponectin and copper were negatively, associated with the risk factors of abnormal health conditions such as diabetes, cardiovascular disease, and oxidative stress [69][70][71]. Additionally, copper has been suggested as a possible mediator of leptin levels regulation [72].…”
Section: Discussionmentioning
confidence: 99%